2011
DOI: 10.1111/j.1464-410x.2011.10258.x
|View full text |Cite
|
Sign up to set email alerts
|

Time‐dependent changes in bladder function and plantar sensitivity in a rat model of fibromyalgia syndrome induced by hydrochloric acid injection into the gluteus

Abstract: What’s known on the subject? and What does the study add? Bladder pain syndrome/interstitial cystitis (BPS/IC) and fibromyalgia syndrome (FMS) often occur concomitantly. In this study, we found that somatic (gluteus)‐to‐visceral (bladder) cross sensitization might underlie bladder hypersensitivity in patients with FMS. OBJECTIVE • To examine the correlation between muscular pain and bladder hypersensitivity in order to clarify the pathogenesis of comorbidity of bladder pain syndrome/interstitial cystitis with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…To investigate effective treatments for FM patients, FM-induced animal models have been made for basic animal research. FM was initially induced by acidic saline injection [21], hydrochloric acid injection [22], or intermittent cold stress [23]. However, these animal models showed comparative recovery within two weeks.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate effective treatments for FM patients, FM-induced animal models have been made for basic animal research. FM was initially induced by acidic saline injection [21], hydrochloric acid injection [22], or intermittent cold stress [23]. However, these animal models showed comparative recovery within two weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Taking stress as one of the main symptoms of fibromyalgia patients, Khasar et al 41 devised the DCG model, which consists of inducing stress through unpredictable sounds. Furuta et al 46 devised the FMS model, SVI/CI, with an intramuscular injection of HCl, pH 4 bilaterally in the gluteal muscles and an injection of intravesical polyethylene catheter + + 1% lidocaine. Green et al 41 proposed the model of FMS, SVI, anxiety, and temporomandibular disorder.…”
Section: Discussionmentioning
confidence: 99%
“…In other reports, a rat model with surgically‐induced endometriosis had reduced micturition thresholds and increased Evans Blue dye extravasation in the bladder, suggesting that bladder hypersensitivity and inflammation might be induced by uterine irritation as a result of endometriosis 32 . Recently, we also have shown that a rat model of FMS induced by HCl injection into the gluteus 33 showed plantar hypersensitivity and bladder overactivity, suggesting the possibility that somatic (gluteus muscle)‐to‐visceral (bladder) cross‐sensitization might underlie bladder hypersensitivity in patients with FMS 34 …”
Section: Neural Cross‐talk In Peripheral and Central Nervous Systemsmentioning
confidence: 97%